2018
DOI: 10.1016/j.expneurol.2018.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with low-dose fimasartan ameliorates NLRP3 inflammasome-mediated neuroinflammation and brain injury after intracerebral hemorrhage

Abstract: Nucleotide-binding and oligomerization domain-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome, which is composed of an NLRP3 domain, the adaptor molecule apoptosis-associated speck-like protein containing a CARD (ASC) domain, and procaspase-1, plays an important role in the immune pathophysiology of the secondary damage induced by intracerebral hemorrhage (ICH). This study aims to investigate whether pre-stroke treatment with fimasartan, an angiotensin II receptor blocker, has anti-inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 58 publications
0
35
0
Order By: Relevance
“…a P < 0.05 vs. sham; b P < 0.05 vs. vehicle; c P < 0.05 vs. Mei. Yang X. et al, 2018;Tan et al, 2019). NLRP3 inflammasome have been demonstrated to significantly increase brain injury and neuroinflammation after stroke (Ma et al, 2018;Jing et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…a P < 0.05 vs. sham; b P < 0.05 vs. vehicle; c P < 0.05 vs. Mei. Yang X. et al, 2018;Tan et al, 2019). NLRP3 inflammasome have been demonstrated to significantly increase brain injury and neuroinflammation after stroke (Ma et al, 2018;Jing et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The nucleotide-binding oligomerization domain, leucine rich, repeat and, pyrin domaincontaining 3 (NLRP3) inflammasome, is a subcellular multiprotein complex that is abundantly expressed in the central nervous system (CNS) [12]. Cryopyrin/NALP3/NLRP3 can sense and respond to a wide range of exogenous and endogenous stimuli, which results in the activation of caspase-1.…”
Section: Introductionmentioning
confidence: 99%
“…Activated caspase-1 and other pro-inflammatory cytokines drive inflammatory responses through diverse downstream signaling pathways, leading to neuronal damage and possibly cell death [13]. We have previously shown that by inhibiting the NLRP3 inflammasome, fimasartan can protect against secondary brain damage in an intracerebral hemorrhage model [12].…”
Section: Introductionmentioning
confidence: 99%
“…The neuroinflammatory response modulates both the pathological changes of demyelination and axonal injury and remyelination and repair 33. It is becoming apparent that inflammatory response activation is essential component of tissue regeneration and remyelination 34, 35. When an eosinophilic mechanism for TSIIA effects on demyelination and remyelination was excluded, we speculated that inflammation may be the key reason for TSIIA efficacy following A. cantonensis infection.…”
Section: Discussionmentioning
confidence: 99%